Understanding Erdogan’s leadership in the «New Turkey» - Fernandes, Raquel dos Santos (2018)
In 2001, the rise of the Justice and Development Party (AKP) in Turkey led to the emergence of a moderate path between Kemalist and Islamic wings. After a first term focused on foreign diplomacy, Erdogan and the party saw their policies gaining broad social support internally, reinforcing their stance in areas of ideological and religious confrontation with secular opposition. Erdogan, although elected president in 2014, has led Turkey on an increasingly conservative route from the standpoint of social values, and less democratic regarding the political language of the state. If Erdogan reveals a conception of state that departs from the democratic values and the ideal of Ataturk’s secular Turkey, and, at the same time, focuses on an Islamic-conservative perspective of society and an authoritarian conception of political power, what explains and stimulates this strategy? This article is based on the premise that perceiving "New Turkey" implies understanding Erdogan’s leadership style, even if it does not exhaust all explanatory variables. From this premise, the goal is to identify and explain internal factors – associated first and foremost with the dualist structure between Turkey’s centre and periphery) – that, along with Erdogan’s individual variables, such as Islamic solidarity and authoritarian tendencies) – put him at the centre of decision-making in Turkey.